(untitled) (Journal of Dhaka Medical College, 2015)
Context: The pineal gland has been described as an endocrine or neuroendocrine gland; however, its functions in humans are still to be defined. Different shapes of the human pineal gland have been identified. Due to its small size and different shapes recognition of this gland is much critical. Besides, due to its cellularity it may be mistaken for a neoplasm. Hence, a sound knowledge on different shapes of the pineal gland is essential for neurosurgeons, radiologists and pathologists for better diagnosis and management of pineal disorders. Methods: A descriptive study was done in the Department of Anatomy, Dhaka Medical College, Dhaka, from July 2009 to June 2010, to see the morphological shape of the human pineal gland. The present study was performed on 60 human pineal glands collected from whole human brains of unclaimed dead bodies that were under postmortem examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. The pineal gland was collected from the brain by meticulous dissection. Then, the shape of the pineal gland was observed under the magnifying glass. Results: In the present study, pea-shaped pineal glands were found 60% in group A, 30% in group B, 5% in both group C and D, while pine cone shaped were found 25% in group A, 37.5% in group B, 25% in group C and 12.5% in group D. Besides, fusiform shaped glands were found 18.2% in group A, 63.6% in group B, 9.1% in both group C and D, where as piriform shaped found 66.7% in group B, and 16.7% in both group C and D. Moreover, cone-shaped glands were found 28.6% in group B, 57.1% in group C and 14.3% in group D. J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 211-214